The impact of inflation in the human levels of poverty and its impact on the performance of human capital In Iraq, for the period 2010- 2013 - Mohammed, Rebar Fatah; Asad, Ismail Aziz; Al-Dabash, Abduallah (Journal of University of Human Development, 2016)
Demonstrates the concept of poverty to deny the poor access to basic basket of goods consisting of food, clothing and housing, in addition to a minimum of other needs, such as health care, transportation and education .and human capital in Iraq suffers from poverty capacity that qualify to contribute to economic development. Research has adopted a hypothesis: that inflation lowers the value of the currency and thus raise the poverty line, which contributes to the increase in the number of poor in the country, which contributes to reducing the skills and abilities of young people to contribute to economic development . The research aims to study the effect of inflation in increasing the number of poor people in Iraq through the study of the impact of inflation and its impact on the poverty line on human capital in Iraq. The research has come to conclusions which: : The poverty line in Iraq, equivalent to about 100 a month, less than the rate of 2 per day, and this means that Iraq’s poor live in deprivation and extreme poverty compared to poor African countries, non-oil, which constitutes the poverty line, up to 30-60 per month. The reasons for the high rates of inflation in Iraq due to the absence of a clearly . The spread of financial and administrative corruption, according to a report in the governance of the international organization which ranked Iraq the last state in transparency. Some styles of gatekeepers and decision-makers to adopt Gatekeepers currency and pumped into the market or hard currency smuggling to neighboring countries . The research was presented proposals including: the development of macroeconomic policy include the ways and methods of reducing poverty in Iraq, and to benefit from the experiences of other countries such as Malaysia, Turkey and Singapore. Reduce the financial and administrative corruption through the dimensions of the corrupt and thieves for managerial positions and refer them to the courts . Open foreign direct investment in all areas of economic and service sectors to provide job opportunities contribute to the reduction of unemployment and poverty reduction.